2015
DOI: 10.1080/08974454.2015.1067174
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inequality and Social Support for Women Prisoners Released to Rural Communities

Abstract: Incarceration and community reentry for rural women reflect gendered processes. We draw upon in-depth semi-structured interviews and focus groups to examine the return of women prisoners to underserved rural communities, while attending to the perspectives of their closest social supporters. Our findings underscore the complexity of the reentry process for rural women and its particular impact on their families. We challenge dominant discourses of personal responsibility that detract from the structura violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In previous studies, we showed that women leaving prison in this environment must rely on informal and insecure networks of family and friends-many of whom also struggle with substance abuse-for financial assistance, housing, and transportation. They experience stigmatization and have trouble avoiding unhealthy relationships and forming supportive bonds in situations of social intimacy and isolation [3]. Women without family often return to abusive partners or attempt to find transitional housing or short-term treatment facilities, most of which are far from their homes [22].…”
Section: Intimate Partner Violence Rurality and Incarceration Of Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we showed that women leaving prison in this environment must rely on informal and insecure networks of family and friends-many of whom also struggle with substance abuse-for financial assistance, housing, and transportation. They experience stigmatization and have trouble avoiding unhealthy relationships and forming supportive bonds in situations of social intimacy and isolation [3]. Women without family often return to abusive partners or attempt to find transitional housing or short-term treatment facilities, most of which are far from their homes [22].…”
Section: Intimate Partner Violence Rurality and Incarceration Of Womenmentioning
confidence: 99%
“…Intimate partner violence (IPV) is a prominent feature in the pathways that lead women such as Cynthia to prison and enhance their risk of mental ill-health, substance use, and recidivism. In New Mexico, a rural state with a complex history of colonialism (i.e., political occupation and economic exploitation), women's experiences of IPV intersect with challenges across multiple social-ecological levels [1]-from individual struggles (e.g., mental distress, substance use), to risky or criminalizing interpersonal relationships, to community characteristics that make it difficult for them to get help (e.g., geographic isolation), all of which are compounded by persistent gender, racial, and economic inequities [2,3]. Given these substantial and intersecting challenges, there is a continued need to understand and plan for the complex correctional and reentry needs of women in these circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, stigma is not only experienced by the person against whom it is perpetrated. Other studies have primarily explored the topic of stigma with family members of incarcerated citizens (Park & Tietjen, 2021;Gueta, 2018;Saunders, 2018;Tadros, Fye & Ray, 2020), and distinguished between groups of currently incarcerated women (Bove & Tyron, 2018;Kellett & Willging, 2011), and gender specific groups of men and women, at a similar stage in their reentry process (Bahr, Armstrong, Gibbs, Harris & Fisher, 2005;Celinska, 2000;Gunn, Sacks & Alexis, 2018;Riccardelli & Mooney, 2018;Willging, Nicdao, Trott & Kellett, 2016). These studies texturize the stigma tapestry, further illuminating the understanding of this unfortunate phenomenon as the basis for its circumvention, diminution, or its elimination.…”
Section: Stigmamentioning
confidence: 99%
“…Changes in law enforcement practices and post-conviction barriers to reentry uniquely affect women (Lam & Harcourt, 2003; Petersilia, 2001; Smith & Visher, 1981). Women prisoners are vulnerable and it is, therefore, necessary to pay particular attention to preventing, monitoring, and treating women-specific health problems, while in prison and upon release (Ramirez, 2016; Willging, Nicdao, Trott, & Kellett, 2015) of the one-quarter of women released from prison fail within 6 months (i.e., have an arrest for a new crime), one-third fail within a year and two-thirds fail five years after release (Willging et al, 2015). Not all prison provide eligible women with trauma treatment, pregnancy programs, and other needed health care services.…”
Section: Resultsmentioning
confidence: 99%